2016
DOI: 10.3390/ijms17101695
|View full text |Cite
|
Sign up to set email alerts
|

CaMKK2 Suppresses Muscle Regeneration through the Inhibition of Myoblast Proliferation and Differentiation

Abstract: Skeletal muscle has a major role in locomotion and muscle disorders are associated with poor regenerative efficiency. Therefore, a deeper understanding of muscle regeneration is needed to provide a new insight for new therapies. CaMKK2 plays a role in the calcium/calmodulin-dependent kinase cascade; however, its role in skeletal muscle remains unknown. Here, we found that CaMKK2 expression levels were altered under physiological and pathological conditions including postnatal myogensis, freeze or cardiotoxin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Depending on the cellular context and stimuli, CAMKK2 activation can exert either an inhibitory or stimulatory effect on cellular differentiation. In this regard, it has been shown that CAMKK2 activation inhibits myoblast [ 48 ] and preadipocyte differentiation [ 49 ], whereas it accelerates monocyte differentiation induced by colony stimulating factor 1 [ 50 ]. Our findings reveal that CAMKK2 suppresses granulocytic differentiation induced by ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cellular context and stimuli, CAMKK2 activation can exert either an inhibitory or stimulatory effect on cellular differentiation. In this regard, it has been shown that CAMKK2 activation inhibits myoblast [ 48 ] and preadipocyte differentiation [ 49 ], whereas it accelerates monocyte differentiation induced by colony stimulating factor 1 [ 50 ]. Our findings reveal that CAMKK2 suppresses granulocytic differentiation induced by ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…A similar inhibitory effect of AICAR on primary bovine myoblasts was also observed [ 132 ]. Furthermore, transfection of C2C12 myoblasts with CamKKβ, an established AMPK activator, resulted in AMPK activation in myoblasts, cell cycle arrest and impaired proliferation as well as impaired subsequent differentiation, and this effect on proliferation and differentiation was AMPK-dependent since it was blocked by dominant-negative AMPK expression [ 133 ]. Together, these in vitro findings suggest that hyperactivation of AMPK in myoblasts blocks muscle proliferation and differentiation.…”
Section: Influence Of Ampk On Skeletal Muscle Regeneration After Imentioning
confidence: 99%
“…In addition, novel_3 and novel_38 were the top 2 expressed novel DEmiRNAs, which targeted 12 and 110 genes, respectively. The target genes CaMKK2 [22], CD9 [23], BAG3 [24]and NUAK2 [25] of novel_3 are related to muscle regeneration. Target gene of novel_38 were not enriched in GO, but the target gene STAT5B was involved in the growth hormone and JAK-STAT signaling pathways, which were associated with skeletal muscle development [26,27].…”
Section: Discussionmentioning
confidence: 99%